Orchestra concert preparation: the impact of knowing the music’s background and having a voice in the decision - Conrade, Amanda (Kansas State University, 2022)
The lessons demonstrated in this report are focused on providing context for the pieces my students would be playing for their upcoming concert. Leading up to these lessons, I provided students with a list of songs from different cultures and had those who were knowledgeable in those cultures share their opinions of which were truly representative of their culture. Another aspect of these lessons included students doing their own research on the more classical pieces to find out more information about what might have been going on when the piece was originally composed and how that might have influenced the composer and their work. Throughout this master’s program I have more finely defined my own philosophy and beliefs of teaching and have learned how to more properly program music for concerts that are developmentally appropriate for my students’ skill levels. Learning about the different philosophies, beliefs, and the history of where music education has been and the possibilities for the future, I found myself recognizing where I agreed with philosophers and where I disagreed. Digging in to my own philosophy, I discovered my passion for how music interacts and connects with communities. I also solidified my belief that music education is meant for everyone, not only those who can afford it as an extra activity. Music education helps develop well rounded individuals who have learned how to reflect, adapt, and make changes as they are needed. These skills taught by music education are highly necessary within society and are constantly needed to be successful in a community. Though these skills are needed throughout many aspects of life, it is also important as a teacher to be able to apply these skills when it comes to concert planning. Throughout this program I have learned about important music study skills and how to apply them when choosing music. These skills include playing through each part, listening to the music, and researching the piece’s and composer’s background. After applying these skills, I have been able to share more information about a piece, conduct more fluidly when it comes to cues, and convey the nuances of each piece my orchestras are playing. Along with more structured prep work for concert pieces, I have also learned that it is okay to drop a piece from a concert when it is not coming together well. When it comes to performances, it is more important for students to feel confident and for the piece to demonstrate the best of their abilities. It is not helpful to try and cram a piece that is either too difficult or just not ready into a concert. By being willing to let a piece go, it helps students with their confident, self-esteem, and willingness to work even harder on the pieces that are still in the performance.
Keywords: Music selection; Music background; Rehearsal